Functional characterization of four novel PAX8 mutations causing congenital hypothyroidism: new evidence for haploinsufficiency as a disease mechanism - Narumi, Satoshi; Araki, Shunsuke; Hori, Naoaki; Muroya, Koji; Yamamoto, Yukiyo; Asakura, Yumi; Adachi, Masanori; Hasegawa, Tomonobu (European journal of endocrinology, 2012)
Background Individuals carrying a heterozygous inactivating PAX8 mutation are affected by congenital hypothyroidism (CH), although heterozygous Pax8 knockout mice are not. It has remained unclear whether CH in PAX8 mutation carriers is caused by haploinsufficiency or a dominant negative mechanism. Objective To report clinical and molecular findings of four novel PAX8 mutations, including one early-truncating frameshift mutation. Subjects and methods Four probands were CH patients. Two had family history of congenital or childhood hypothyroidism. Three probands were diagnosed in the frame of newborn screening for CH, while one had a negative result in screening but was diagnosed subsequently. Three had thyroid hypoplasia and one had a slightly small thyroid with low echogenicity. For these probands and their family members, we sequenced PAX8 using a standard PCR-based method. Pathogenicity of identified mutations was verified in vitro. Results We found four novel heterozygous PAX8 mutations in the four probands: L16P, F20S, D46SfsX24, and R133Q. Family studies showed four additional mutation carriers, who were confirmed to have high serum TSH levels. Expression experiments revealed that three mutations (L16P, F20S, and R133Q) had defects in target DNA binding, while D46fs had protein instability that was rescued by the proteasome inhibitor MG132. All four mutations had reduced transactivation on the thyroglobulin promoter, supporting that they were inactivating mutations. Conclusion D46fs is the first PAX8 mutation with confirmed protein instability. Our clinical and in vitro findings together suggest that pure PAX8 haploinsufficiency can cause CH in humans.